Isolation and diagnosis of pathogenic bacteria from the intestine of carp (Cyprinus carpio) from Tigris River in the city of Mosul - Nawal Obeidi; Somaya Al - Dabbagh (College of Education for Pure Sciences, 2012)
ABSTRACT Eighty samples were collected from intestine of Cyprinus carpio fish from Tigres river passing through Mosul city during the period from October 2009 to October 2010. In this study Intestinal samples of fish showed bacterial growth and yielded 74 isolates 92,5%, 56 isolates (70%) were found belong to eight genus of Gram-negative bacteria and 18 isolates (22.5%) of Gram-positive bacteria. They are 14 isolates (%17.5) Aeromonas hydrophilia, 13(%16.25) Pseudomonas aeruginosa, 12(%15) Esherichia coli, 6(%7.5) Klebsiella pneumonia, 5(%6.25) Enterobacter aerogenes, 3(%3.7) Citrobacter freundii, 1 (%1.25) Proteus spp. 2(%2.5) Flavobacterium spp. Gram positive included 5(%6.25) Staphylococcus spp. 4(%5) Enterococcus fecalis. 4(%5) Listeria spp., 3(%3.7) Bacillus spp., 2(%2.5) Corynebacterium spp. The result of sensitivity test was variable. Most species of bacterial isolated were resistant to ampicillin but sensitive to ciprofloxacin other bacterial isolated give variable results between resistant and sensitiv to other types of antibiotic used in this study.